Method for preparing high-modulus sodium silicate and co-producing white carbon black from rice hull ash
High-modulus sodium silicate solution is prepared by acidification treatment and ultrasonic neutralization reaction of rice husk ash. Combined with a bipolar membrane electrodialysis system, the acid and alkali media are recovered, which solves the problems of high energy consumption and pollution of traditional processes and realizes the high-value utilization and green production of rice husk ash. The product is suitable for rubber reinforcement and other fields.
Patent Information
- Application Number
- CN202510922551.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-10-24
AI Technical Summary
Traditional processes for producing high-modulus water glass sodium silicate and precipitated silica are characterized by high energy consumption, significant pollution, and difficulty in modulus control. The purification and utilization of rice husk ash are also characterized by complex processes, high costs, and heavy pollution.
High-modulus sodium silicate solution was prepared by pulverizing rice husk ash, followed by acidification and purification. This solution was then subjected to an ultrasonic-assisted neutralization reaction. Combined with plate and frame filtration and countercurrent washing, silica was produced. The filtrate was electrolyzed through a bipolar membrane electrodialysis system to recover the acid and alkali media for recycling.
It realizes the efficient resource utilization of rice husk ash, reduces production costs and environmental impact, provides a green production process, and the product has excellent specific surface area and oil absorption properties, making it suitable for high-end applications such as rubber reinforcement.
Smart Images

Figure CN120829166A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of material science, and particularly relates to a preparation method for preparing high modulus sodium silicate and co-producing white carbon black from rice husk ash. BACKGROUND
[0002] Sodium silicate solution and white carbon black (precipitated silica) are important industrial raw materials, which are widely used in rubber, paint, detergent, casting and other fields. The traditional production process of high modulus sodium silicate is to melt and react quartz sand with sodium carbonate or sodium hydroxide at high temperature (1300-1500℃), which has problems of high energy consumption, serious pollution (CO2 emission), and difficult modulus control. The traditional production method of white carbon black mostly uses sulfuric acid precipitation method, which consumes a large amount of high-purity sodium silicate and sulfuric acid, and has high cost and low resource utilization rate.
[0003] Meanwhile, rice husk ash is a waste after burning of rice husk, which has potential utilization value due to its rich amorphous silicon dioxide (content of 85%-95%). However, the existing technology has problems of complex process, high cost, and serious pollution in purification and utilization of rice husk ash. SUMMARY
[0004] Therefore, the present application aims to provide a preparation method for preparing high modulus sodium silicate and co-producing white carbon black from rice husk ash, which realizes efficient resource utilization of waste such as rice husk ash and high-salt wastewater, and reduces raw material cost, energy consumption and pollution by using a green process to produce high modulus sodium silicate and white carbon black.
[0005] In order to achieve the above technical purposes, the technical scheme adopted by the present application is as follows: a preparation method for preparing high modulus sodium silicate and co-producing white carbon black from rice husk ash, comprising:
[0006] The rice husk ash is crushed to 100-200 meshes and then conveyed to an acid washing tank, and acidification treatment is performed in the acid washing tank to obtain purified rice husk ash powder with SiO2 content of ≥90%;
[0007] The purified rice husk ash powder is conveyed to a reaction kettle, 5wt%-15wt% caustic soda produced by bipolar membrane electrolysis is added according to the molar ratio of SiO2:NaOH 1:2, and sodium silicate solution with modulus of 2.0-4.0 is obtained;
[0008] The sodium silicate solution is conveyed to an ultrasonic reactor, 1wt%-15wt% sulfuric acid solution is slowly added under the assistance of ultrasonic waves with a frequency of 40 kHz, and neutralization reaction is performed. After the reaction is completed, the solution is conveyed to a plate and frame filter press for filtration, and silica silicon gel and filtrate are obtained;
[0009] The silica silicon gel is washed with 50℃-65℃ deionized water in countercurrent until the Na2SO4 content is ≤0.05%, and then the silica silicon gel is conveyed to a spray dryer for drying, and white carbon black with specific surface area of 150m2 / g ~ 250 m 2 / g, DBP oil absorption value 2.0 mL / g ~ 3.5 mL / g of white carbon black product;
[0010] The filtrate is transported to a bipolar membrane electrodialysis system for electrolysis treatment, and 5wt% ~ 15wt% of the recovered NaOH solution is recycled, and 1wt% ~ 15wt% of the recovered H2SO4 solution is returned to the ultrasonic reactor for recycling.
[0011] In some embodiments, the rice husk ash is crushed to 100 mesh ~ 200 mesh and then transported to an acid washing tank, and an acidification treatment is performed in the acid washing tank to obtain a purified rice husk ash powder with a SiO2 content of ≥ 90%, including:
[0012] 1wt% ~ 5wt% of dilute sulfuric acid is added for acidification treatment at 50°C ~ 95°C for 30min ~ 90min, and then washed with deionized water until pH = 6.5 ~ 7.0, and then dried to obtain a purified rice husk ash powder with a SiO2 content of ≥ 90%.
[0013] In some embodiments, the purified rice husk ash powder is transported to a reaction kettle, 32wt% of electrolyte alkali is added and mixed according to a SiO2: NaOH molar ratio of 1:2 to obtain a sodium silicate solution with a modulus of 2.0 ~ 4.0, including:
[0014] The reaction kettle is equipped with a variable frequency speed stirrer to mix at a stirring speed of 80rpm ~ 120rpm, the viscosity of the solution is monitored in real time during the reaction and maintained within the range of 200cP ~ 300cP, and finally a sodium silicate solution with a modulus of 2.0 ~ 4.0 is obtained.
[0015] In some embodiments, the sodium silicate solution is transported to an ultrasonic reactor, 1wt% ~ 15wt% of sulfuric acid solution is slowly added under the assistance of ultrasonic waves with a frequency of 40kHz, and a neutralization reaction is performed, including:
[0016] A multi-stage gradient acid addition method is used, 40% of the total sulfuric acid solution is added at a flow rate of 1.5mL / min, and the remaining 60% of the sulfuric acid solution is added at a flow rate of 0.8mL / min, the reaction endpoint pH = 9.5 ~ 11 is controlled, the reaction temperature is maintained at 80±15°C, and the ultrasonic power density is maintained at 0.5W / cm 3 ~ 0.8W / cm 3 .
[0017] In some embodiments, after the neutralization reaction is completed, it is transported to a plate and frame filter press for filtration to obtain a silica silica gel and a filtrate, including:
[0018] Circulating filtration at 0.3-0.6 MPa for 30 min;
[0019] Main filtration at 0.6-0.8 MPa for 30-180 min;
[0020] Final filtration at 0.8 MPa for 10-30 min;
[0021] The temperature of the filter cake is maintained at 60-65 ℃ during filtration, 150-300 mesh filter cloth is used, and the moisture content of the obtained silica silica gel is controlled at 45-55%, and the content of suspended solids in the filtrate is ≤50 ppm.
[0022] In some embodiments, after the silica silica gel is washed with 50-65 ℃ deionized water to a Na2SO4 content of ≤0.05%, it is sent to a spray dryer for drying, to obtain a white carbon black product with a specific surface area of 150 m 2 / g
[0023] 250 m 2 / g, a DBP oil absorption value of 2.0-3.5 mL / g, including:
[0024] The deionized water and the silica silica gel are contacted in a cross-flow mode at a mass ratio of 3:1, the washing time is 15-20 min, and the pH value during washing is 6.5-7.5;
[0025] The obtained white carbon black product has a median particle size D50 of 4.0
[0026] -8.0 μm, and a particle size distribution Span value of ≤1.2.
[0027] In some embodiments, the filtrate is sent to a bipolar membrane electrodialysis system for electrolysis treatment, the recovered 5wt% NaOH solution is recycled, and the recovered 10wt% H2SO4 solution is returned to the ultrasonic reactor for recycling, including:
[0028] The bipolar membrane electrodialysis system is used, the current density is controlled at 400-1000 A / m, the operating temperature is 35-45 ℃, and the feed flow rate is 0.2-1.2 m / s;
[0029] The 5-15wt% NaOH solution produced by electrolysis is recycled after online concentration detection;
[0030] The 10wt% H2SO4 solution is returned to the ultrasonic reactor after 0.2 μm precision filtration.
[0031] In some embodiments, the bipolar membrane electrodialysis system adopts a bipolar membrane electrolytic cell with a three-chamber structure, the operating voltage is 1.5V per membrane pair to 2.5V per membrane pair, and the salt chamber adopts a 10% to 15% mass concentration Na2SO4 solution as the raw material liquid.
[0032] Compared with the prior art, the present application has the beneficial effects that: the present application provides a preparation method for preparing high-modulus sodium silicate and co-producing white carbon black from rice hull ash, comprising: pulverizing the rice hull ash and then performing acidification treatment to obtain purified rice hull ash powder; reacting the purified rice hull ash powder with 5wt% to 15wt% caustic soda produced by bipolar membrane electrolysis to obtain a sodium silicate solution; performing neutralization reaction on the sodium silicate solution in an ultrasonic auxiliary manner with 1wt% to 15wt% sulfuric acid solution, and then filtering to obtain silica silica gel and filtrate; washing and drying the silica silica gel to obtain white carbon black products; and performing electrolysis treatment on the filtrate by a bipolar membrane electrodialysis system, and recycling the recovered alkali liquor and acid liquor. The method realizes resource utilization of the rice hull ash and recycling of the reaction medium, and forms a green production process. BRIEF DESCRIPTION OF DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or the prior art description. Obviously, the drawings in the following description are only some embodiments of the present application, and all other drawings obtained by those skilled in the art without creative labor are also within the scope of protection of the present application.
[0034] Figure 1 is a flow chart of the preparation method described in the detailed description. DETAILED DESCRIPTION
[0035] The present application will be further described in detail below in combination with the drawings and embodiments. It is particularly pointed out that the following embodiments are only used to illustrate the present application, but do not limit the scope of the present application. Similarly, the following embodiments are only some embodiments of the present application, not all embodiments, and all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0036] Please refer to Figure 1 The present embodiment provides a preparation method for preparing high-modulus sodium silicate and co-producing white carbon black from rice hull ash, comprising:
[0037] After the rice hull ash is pulverized to 100 meshes to 200 meshes, it is transported to an acid washing tank, and acidification treatment is performed in the acid washing tank to obtain purified rice hull ash powder with a SiO2 content of ≥90%;
[0038] The purified rice husk ash powder is transferred to a reactor, and 5 wt% electrolyte alkali is added and mixed in a SiO2:NaOH molar ratio of 1:2 to obtain a sodium silicate solution with a modulus of 2.0 to 4.0;
[0039] The sodium silicate solution was transferred to an ultrasonic reactor, and a 15 wt% sulfuric acid solution was slowly added under the assistance of ultrasound at a frequency of 40 kHz to carry out a neutralization reaction. After the reaction was completed, the solution was transferred to a plate and frame filter press for filtration to obtain silica gel and filtrate;
[0040] The silica gel was washed with 50℃~65℃ deionized water in reverse flow until the Na2SO4 content was ≤0.05%, and then transported to a spray dryer for drying to obtain a specific surface area of 150m 2 / g~250m 2 / g, white carbon black products with DBP oil absorption value of 2.0mL / g to 3.5mL / g;
[0041] The filtrate is transported to a bipolar membrane electrodialysis system for electrolysis treatment, the recovered 5wt% to 15wt% NaOH solution is recycled, and the recovered 1wt% to 15wt% H2SO4 solution is returned to the ultrasonic reactor for recycling.
[0042] In this embodiment, the process of preparing high modulus sodium silicate and co-producing white carbon black from rice husk ash can be understood as follows: after the rice husk ash is crushed to 100 mesh to 200 mesh, acidification treatment is performed to obtain purified rice husk ash powder with a SiO2 content of ≥90%; the purified rice husk ash powder is mixed with 5wt% electrolyte alkali in a reactor at a SiO2:NaOH molar ratio of 1 to 2 to prepare a sodium silicate solution with a modulus of 2.0 to 4.0; the solution is slowly added with 10wt% sulfuric acid solution in a 40kHz ultrasonic reactor for neutralization reaction, and filtered through a plate and frame filter press to obtain silica gel and a filtrate containing Na2SO4; the silica gel is countercurrent washed with deionized water at 50°C to 65°C until the Na2SO4 content is ≤0.05%, and then dried in a spray dryer to obtain a specific surface area of 150m 2 / g~250m 2 / g, and a white carbon black product with a DBP oil absorption value of 2.0mL / g to 3.5mL / g; the filtrate is electrolyzed by a bipolar membrane electrodialysis system, and the recovered 5wt% NaOH solution is returned to the reactor for use, and the 1wt% H2SO4 solution is returned to the ultrasonic reactor for recycling.
[0043] This embodiment efficiently purifies rice husk ash through acidification treatment and directly prepares a high-modulus sodium silicate solution using an electrolyte alkaline reaction, overcoming the high energy consumption disadvantage of the traditional quartz sand melting method. Ultrasonic-assisted neutralization reaction promotes the uniform precipitation of silica gel, and plate and frame filter pressing and countercurrent washing processes are combined to ensure that the white carbon black product has excellent specific surface area and oil absorption properties.
[0044] The embodiment not only realizes high-value utilization of agricultural waste, but also significantly reduces production cost and environmental load through medium circulation and energy recovery, thereby providing a technical solution for green production of sodium silicate and white carbon black.
[0045] In some embodiments, the rice husk ash is crushed to 100-200 mesh and then transported to an acid washing tank, and an acidification treatment is performed in the acid washing tank to obtain a purified rice husk ash powder with a SiO2 content of ≥90%, including:
[0046] 1wt% to 5wt% dilute sulfuric acid is added and acidification treatment is performed at 50-95°C for 30-90min, and then the product is washed with deionized water until pH=6.5-7.0 and dried to obtain a purified rice husk ash powder with a SiO2 content of ≥90%.
[0047] In this embodiment, in the raw material pretreatment stage, the rice husk ash is crushed and then subjected to acidification treatment: 1wt% to 5wt% dilute sulfuric acid is added and acidification treatment is performed at 50-95°C for 30-90min, and finally washed with deionized water until pH=6.5-7.0 and dried to obtain a purified rice husk ash powder with a SiO2 content of ≥90%. This acidification treatment effectively removes metal impurities such as iron and aluminum by controlling the acid concentration and temperature in stages, which can reduce acid consumption compared to traditional high-concentration acid washing, and the obtained powder has more uniform chemical activity.
[0048] This embodiment optimizes the acidification treatment process parameters, uses 1wt% to 5wt% low-concentration sulfuric acid to treat rice husk ash at 50-95°C, significantly reduces acid washing energy consumption and waste acid production while ensuring the purification effect of silicon dioxide (SiO2≥90%). Precise control of acidification temperature and time window effectively removes metal impurities such as iron and aluminum without damaging the active structure of amorphous silicon dioxide, and washing to pH 6.5-7.0 ensures the chemical stability of the powder. This process is more in line with the principles of green chemistry compared to traditional high-concentration acid washing, providing an ideal raw material basis for subsequent preparation of high-reactivity sodium silicate solution, while simplifying the wastewater treatment process, making the overall process more easily implemented in industry.
[0049] In some embodiments, the purified rice husk ash powder is transported to a reaction kettle, 5wt% to 15wt% caustic soda (preferably 10wt%) produced by bipolar membrane electrolysis is added and mixed according to the molar ratio of SiO2:NaOH 1:2 to obtain a sodium silicate solution with a modulus of 2.0-4.0, including:
[0050] The reaction kettle is equipped with a variable frequency speed stirrer to mix at a stirring speed of 80 rpm to 120 rpm. The viscosity of the solution is monitored in real time during the reaction and maintained in the range of 200 cP to 300 cP. Finally, a sodium silicate solution with a modulus of 2.0 to 4.0 is obtained.
[0051] In this embodiment, in the sodium silicate synthesis stage, the purified rice husk ash powder is mixed with 10 wt% electrolyte alkali at a SiO2:NaOH molar ratio of 1:2. The mixture is reacted at 0.3 MPa, 90°C to 110°C for 1.5 h by a variable frequency speed stirrer at a stirring speed of 80 rpm to 120 rpm. The viscosity of the solution is monitored in real time and maintained in the range of 200 cP to 300 cP. Finally, a sodium silicate solution with a modulus of 2.0 to 4.0 is obtained.
[0052] In this embodiment, by precisely controlling the synergistic effect of reaction pressure, temperature and stirring speed, and cooperating with real-time viscosity monitoring, the reaction system is always in the best mass and heat transfer state, so that the SiO2 dissolution and polymerization reaction are optimized synchronously. The constant pressure condition promotes the penetration of the alkali solution into the pores of amorphous silicon dioxide. The variable frequency stirring realizes the uniform dispersion of the reactants without damaging the molecular structure. The viscosity monitoring ensures the stability of the solution polymerization degree. Finally, a high-quality sodium silicate solution with a precisely controllable modulus is obtained. Compared with the traditional melting method, the reaction time is shortened by more than 80%, and the modulus fluctuation problem caused by local over-reaction is avoided.
[0053] In some embodiments, the sodium silicate solution is transported to an ultrasonic reactor, and a 10 wt% sulfuric acid solution is slowly added under the assistance of ultrasonic waves at a frequency of 40 kHz to perform a neutralization reaction, including:
[0054] A multi-stage gradient acid addition method is used. First, 40% of the total sulfuric acid solution is added at a flow rate of 1.5 mL / min, and then the remaining 60% of the sulfuric acid solution is added at a flow rate of 0.8 mL / min. The reaction endpoint pH is controlled at 9.5 to 11, and the reaction temperature is maintained at 80±15°C. The ultrasonic power density is maintained at
[0055] 0.5 W / cm 3 to 0.8 W / cm 3 .
[0056] In this embodiment, in the stage of adjusting modulus and co-producing with white carbon black, the sodium silicate solution is transported to a 40 kHz ultrasonic reactor, and a multi-stage gradient acid addition method is adopted to realize uniform precipitation of silica silica gel. Through the synergistic effect of ultrasonic cavitation effect and gradient acid addition, the precise control of acid-base neutralization reaction is realized at the molecular scale. The microjet generated by 40 kHz ultrasonic promotes the uniform dispersion of reactants, the multi-stage acid addition strategy avoids the agglomeration of gel caused by local over-acidification, and strict pH and temperature control ensures the ordered polymerization of silica silica gel.
[0057] Compared with conventional stirring neutralization, the acid consumption of this embodiment can be reduced by more than 15%, the obtained gel has a more regular network structure and a narrower particle size distribution, which lays a foundation for subsequent preparation of high-dispersion white carbon black, and the ultrasonic assistance significantly shortens the reaction induction period, making the overall production efficiency improve by more than 30%.
[0058] In some embodiments, after the neutralization reaction is completed, it is transported to a plate and frame filter press for filtration to obtain silica silica gel and filtrate, including:
[0059] Circulating filtration pre-press filtration for 30 min under a pressure of 0.3 MPa to 0.6 MPa;
[0060] Rising to 0.6 MPa to 0.8 MPa main pressure filtration for 30 min to 180 min;
[0061] Final pressure filtration for 10 min to 30 min at 0.8 MPa;
[0062] The temperature of the filter cake is maintained at 60°C to 65°C during the filtration process, and a filter cloth with a mesh size of 150 to 300 is used. The water content of the obtained silica silica gel is controlled at 45% to 55%, and the suspended solids content in the filtrate is ≤50 ppm.
[0063] In this embodiment, through the synergistic effect of the gradient pressure rising strategy and constant temperature control, uniform molding of the filter cake is realized in the pre-pressing stage, the main liquid phase separation is completed in the main pressure stage, and the pore structure of the gel is precisely controlled in the final pressure stage. The constant temperature condition maintains the stability of the gel rheological properties, and the filter cloth with a specific mesh size ensures the filtration accuracy while avoiding filter cake cracking.
[0064] Compared with traditional constant pressure filtration, the filtration efficiency of this embodiment can be improved by more than 40%, and the obtained silica silica gel has a more uniform pore distribution and an ideal water content, which not only ensures the optimal energy consumption of subsequent drying, but also maintains the integrity of the gel active sites. At the same time, the filtrate with ultra-low suspended solids content can be directly reused in the electrolysis process, realizing resource closed-loop utilization.
[0065] In some embodiments, after the silica silica gel is washed with 50°C to 65°C deionized water until the Na2SO4 content is ≤0.05%, it is transported to a spray dryer for drying to obtain silica silica gel with a specific surface area of 150 m 2 / g
[0066] ~ 250 m 2 / g, a white carbon black product with a DBP oil absorption value of 2.0 mL / g~3.5 mL / g, including:
[0067] The deionized water and the silica silica gel are countercurrently contacted at a mass ratio of 3:1, the washing time is 15 min~20 min, and the pH value during the washing process is 6.5~7.5;
[0068] The obtained white carbon black product has a median particle size D50 of 4.0
[0069] μm~8.0 μm, and a particle size distribution Span value ≤1.2.
[0070] In the present embodiment, in the white carbon black preparation stage, the silica silica gel is countercurrently washed with 50℃~65℃ deionized water at a mass ratio of 3:1 for 15 min~20 min until the Na2SO4 content is ≤0.05%, the pH value is maintained at 6.5~7.5 during the washing process, then dried with a spray dryer, and finally treated with a turbo air flow crusher, to obtain a white carbon black product with a specific surface area of 150 m 2 / g~250 m 2 / g, a DBP oil absorption value of 2.0 mL / g~3.5 mL / g, and a D50 of 4.0 μm~8.0 μm.
[0071] In the present embodiment, by optimizing the post-treatment process of the silica silica gel, the residual Na2SO4 is effectively removed without damaging the gel network structure under the mild conditions of 50℃~65℃ countercurrent washing, and the active surface silanol is maintained by accurately controlling the pH value range (6.5~7.5). The spray drying process can better maintain the porous structure compared with the traditional oven drying, and the turbo air flow crushing makes the product obtain an ideal particle size distribution (Span ≤1.2) of 4.0 μm~8.0 μm. This balanced physical property makes the white carbon black product have high specific surface area and excellent dispersibility, and is particularly suitable for high-end application fields such as rubber reinforcement. The entire post-treatment process realizes energy optimization while ensuring product quality, and forms a complete technical chain seamlessly connected with the front-end process.
[0072] In some embodiments, the filtrate is transported to a bipolar membrane electrodialysis system for electrolysis treatment, the recovered 10wt% NaOH solution is recycled, and the recovered 10wt% H2SO4 solution is returned to the ultrasonic reactor for recycling, including:
[0073] The bipolar membrane electrodialysis system is used, the current density is controlled to be 400 A / m~1000 A / m, the operating temperature is 35℃~45℃, and the feed liquid flow rate is 0.2 m / s~1.2 m / s;
[0074] The 10wt% NaOH solution produced by electrolysis is recycled after online concentration detection;
[0075] The 10wt% H2SO4 solution is returned to the ultrasonic reactor after 0.2 mu m precision filtration.
[0076] In the by-product recovery stage, the filtrate is delivered to the bipolar membrane electrodialysis system, the current density is controlled at 400 A / m 2 ~ 1000 A / m 2 , the operating temperature is 35 DEG C ~ 45 DEG C, the feed liquid flow rate is 0.2 m / s ~ 1.2 m / s, electrolysis is carried out. The recovered 10wt% NaOH solution is recycled for water glass synthesis after online concentration detection, and the 10wt% H2SO4 solution is returned to the ultrasonic reactor after 0.2 mu m precision filtration.
[0077] The bipolar membrane electrodialysis system in this embodiment realizes efficient electrolytic separation of Na2SO4 solution under mild conditions, and the precise control of current density ensures the ion migration efficiency, and the constant temperature operation avoids the risk of membrane fouling. The recovered 10wt% NaOH and 10wt% H2SO4 solution can be directly recycled for the previous process, forming a complete material circulation system. Compared with the traditional process, the integrated recovery system reduces the consumption of fresh acid and alkali by more than 70%, and truly realizes the resource utilization target of zero emission of waste gas, waste water and waste residue.
[0078] In some embodiments, the bipolar membrane electrodialysis system adopts a three-chamber structure bipolar membrane electrolytic cell, the operating voltage is 1.5 V / membrane pair ~ 2.5 V / membrane pair, and the salt chamber adopts 10% ~ 15% Na2SO4 solution as the electrolyte.
[0079] In this embodiment, by optimizing the structural parameters of the bipolar membrane electrodialysis system, the three-chamber structure bipolar membrane electrolytic cell and the precisely controlled 0.2mm ~ 1.2mm inter-membrane spacing work together to form a stable ion migration channel under the operating voltage of 1.5 V / membrane pair ~ 2.5 V / membrane pair, which not only ensures the high separation efficiency of Na + and SO4 2- , but also avoids the risk of short circuit of the membrane stack. Using 10% ~ 15% Na2SO4 as the salt chamber electrolyte can maintain stable current conduction and prevent electrode corrosion. This embodiment makes the bipolar membrane electrodialysis system maintain excellent membrane flux stability in long-term operation, compared with the traditional electrodialysis device, the energy consumption can be reduced under the same processing capacity, the membrane pollution rate is significantly slowed down, and the continuous operation cycle of the device is prolonged, which provides reliable guarantee for the industrial implementation of the acid and alkali recovery process.
[0080] By adopting the above technical scheme, the present application is different from the prior art and has the following beneficial effects:
[0081] The application realizes high-value utilization of agricultural waste and green cyclic production by preparing high modulus sodium silicate and co-producing white carbon black from rice husk ash. The acidification treatment is used to efficiently purify rice husk ash powder, and high modulus sodium silicate solution is directly prepared through electrolyte alkali reaction, which overcomes the high energy consumption defect of the traditional quartz sand melting method. The ultrasonic assisted neutralization reaction promotes the uniform precipitation of silica silica gel, and the plate and frame filter pressing and countercurrent washing process ensures that the white carbon black product has excellent specific surface area and oil absorption performance.
[0082] The bipolar membrane electrodialysis system adopts a three-chamber structure of a bipolar membrane electrolytic cell, optimizes the membrane spacing and operating voltage parameters, ensures the ion migration efficiency while reducing energy consumption. The above technical scheme significantly reduces production cost and environmental load through medium circulation and energy recovery, provides an industrialized implementation technical scheme for green production of sodium silicate and white carbon black, and realizes the resource utilization target of zero emission of waste gas, waste water and waste residue.
[0083] In addition, each functional unit in each embodiment of the application can be integrated into one processing unit, or each unit can exist physically, or two or more units can be integrated into one unit. The integrated unit can be realized in the form of hardware or in the form of a software functional unit.
[0084] If the integrated unit is realized in the form of a software functional unit and sold or used as an independent product, it can be stored in a computer readable storage medium. Based on this understanding, the technical solutions of the application essentially or the parts that contribute to the prior art or all or part of the technical solutions can be embodied in the form of a software product, which is stored in a storage medium and includes a plurality of instructions for causing a computer device (which can be a personal computer, a server, or a network device, etc.) or a processor to execute all or part of the steps of the embodiments of the method of the application. The aforementioned storage medium includes: a U disk, a mobile hard disk, a read-only memory (ROM, Read-Only Memory), a random access memory (RAM, Random Access Memory), a magnetic disk or an optical disk, and various program code storage media.
[0085] The above only describes some embodiments of the application, and does not limit the protection scope of the application, and any equivalent device or equivalent process transformation made by using the content of the specification and drawings, or direct or indirect application in other related technical fields, are also included in the patent protection scope of the application.
Claims
1. A method for preparing high modulus sodium silicate coproducing white carbon black from rice husk ash, characterized in that, The method comprises the following steps: The rice husk ash is crushed to 100-200 meshes and then is transported to an acid washing tank, and acidification treatment is performed in the acid washing tank to obtain purified rice husk ash powder with SiO2 content of ≥90%; The purified rice husk ash powder is transported to a reaction kettle, 5-15wt% caustic soda produced by bipolar membrane electrolysis is added and mixed according to the molar ratio of SiO2:NaOH of 1:2 to obtain a sodium silicate solution with a modulus of 2.0-4.0; The sodium silicate solution is transported to an ultrasonic reactor, 1wt%-15wt% sulfuric acid solution is slowly added under the assistance of ultrasonic waves with a frequency of 40 kHz to perform neutralization reaction, and after the reaction is completed, the solution is transported to a plate-and-frame filter press to be filtered to obtain silica silica gel and filtrate; The silica silica gel is washed countercurrently with 50°C to 65°C deionized water until the Na2SO4 content is ≤0.05%, and then is delivered to a spray dryer for drying, to obtain a white carbon black product with a specific surface area of 150 m 2 / g to 250 m 2 / g, a DBP oil absorption value of 2.0 mL / g to 3.5 mL / g. The filtrate is transported to a bipolar membrane electrodialysis system to perform electrolysis treatment, and 5wt%-15wt% NaOH solution recovered is recycled, and 1wt%-15wt% H2SO4 solution recovered is returned to the ultrasonic reactor for recycling.
2. The method of claim 1, wherein the rice hull ash is prepared by the method comprising: The method comprises the following steps: 1-5wt% dilute sulfuric acid is added for acidification treatment at 50-95°C for 30-90 min, and after washing with deionized water until the pH value is 6.5-7.0, drying is performed to obtain purified rice husk ash powder with SiO2 content of ≥90%.
3. The method of claim 1, wherein the rice hull ash is prepared by the method comprising: The purified rice husk ash powder is transported to a reaction kettle, 5wt%-15wt% caustic soda produced by bipolar membrane electrolysis is added and mixed according to the molar ratio of SiO2:NaOH of 1:2 to obtain a sodium silicate solution with a modulus of 2.0-4.0, which comprises the following steps: Stirring reaction is performed at 0.3 MPa and 90-110°C for 1.5 h, a variable-frequency speed regulator is provided in the reaction kettle to perform mixing reaction at a stirring speed of 80-120 rpm, the viscosity of the solution is monitored in real time during the reaction and is maintained in the range of 200-300 cP, and finally a sodium silicate solution with a modulus of 2.0-4.0 is obtained.
4. The method of claim 1, wherein the rice hull ash is prepared by the method comprising: The sodium silicate solution is transported to an ultrasonic reactor, 1wt%-15wt% sulfuric acid solution is slowly added under the assistance of ultrasonic waves with a frequency of 40 kHz to perform neutralization reaction, which comprises the following steps: A multi-stage gradient acid addition mode is adopted, 40% of the total sulfuric acid solution is added at a flow rate of 1.5 mL / min, and the remaining 60% of the sulfuric acid solution is added at a flow rate of 0.8 mL / min, the reaction end point pH value is controlled to be 9.5-11, the reaction temperature is maintained at 80±15°C, and the ultrasonic power density is maintained at 0.5 W / cm 3 ~ 0.8 W / cm 3 .
5. The method for preparing high modulus sodium silicate and co-producing white carbon black from rice husk ash according to claim 4, characterized in that: After the neutralization reaction is completed, the solution is transported to a plate-and-frame filter press to be filtered to obtain silica silica gel and filtrate, which comprises the following steps: Circulating filtration is performed at 0.3-0.6 MPa for 30 min to pre-press filter; The pressure is increased to 0.6-0.8 MPa to perform main filtration for 30-180 min; Final filtration is performed at 0.8 MPa for 10-30 min; The temperature of the filter cake is kept at 60-65℃ during the filtration process, 150-300 mesh filter cloth is used, the water content of the obtained silica silica gel is controlled at 45-55%, and the content of suspended solids in the filtrate is ≤50ppm.
6. The method of claim 1, wherein the rice hull ash is prepared by the method comprising: The silica silica gel is washed countercurrently with 50°C to 65°C deionized water until the Na2SO4 content is < 0.05%, and then is delivered to a spray dryer for drying, to obtain a white carbon black product having a specific surface area of 150 m 2 / g to 250 m 2 / g, a DBP oil absorption value of 2.0 mL / g to 3.5 mL / g. The deionized water and the silica silica gel are contacted in a cross-flow mode at a mass ratio of 3:1, the washing time is 15-20 min, and the pH value during the washing process is 6.5-7.5; The obtained white carbon black product has a median particle size D50 of 4.0-8.0μm and a particle size distribution span value ≤1.
2.
7. The method of claim 1, wherein the rice hull ash is prepared by a method comprising: The filtrate is transported to a bipolar membrane electrodialysis system for electrolysis treatment, 5-15wt% of the recovered NaOH solution is recycled, 1-15wt% of the recovered H2SO4 solution is returned to the ultrasonic reactor for recycling, including: The bipolar membrane electrodialysis system is used, the current density is controlled at 400-1000A / m, the operating temperature is 35-45℃, and the feed liquid flow rate is 0.2-1.2m / s; The 5-15wt% NaOH solution produced by electrolysis is recycled after online concentration detection; The 1-15wt% H2SO4 solution is returned to the ultrasonic reactor after 0.2μm precision filtration.
8. The method of claim 7, wherein the rice hull ash is prepared by a method comprising: The bipolar membrane electrodialysis system uses a three-chamber bipolar membrane electrolytic cell, the operating voltage is 1.5-2.5V per membrane pair, and a 10-15wt% Na2SO4 solution is used as the raw material liquid in the salt chamber.
Citation Information
Cited By
Method for preparing silicon dioxide for food additive by using rice hull ash
CN121493997A